Conhecimento e comportamento de acadêmicos de enfermagem acerca da prevenção de infecções sexualmente transmissíveis - Caroline Clemente Merenhque; Camila Nunes Barreto; Luiza Cremonese; Graciela Dutra Sehnem; Carolina Carbonell Demori; Eliane Tatsch Neves (Universidade Federal de Santa Maria, 2020)
Objective: to describe nursing students' knowledge and behavior about sexually transmitted infections. Method: three group sessions were held in November 2019, with the participation of nursing students. The analysis of the information was based on the analysis of operative content. Results: the university students demonstrated knowledge about sexually transmitted infections. Regarding risk perception, they feel vulnerable, although they are aware of protection. The academic environment provides greater susceptibilities, as well as social media. During graduation, they expanded their knowledge and began to be more careful, especially when diagnosing new infections of users of the health system met in practical class and internship. Conclusion: the adoption of safe practices is associated with acquired knowledge and the verification of new cases of users in learning scenarios. It is essential that educational institutions, especially universities, develop educational actions towards students.